2015
DOI: 10.1016/j.jtcvs.2015.08.092
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity for lung cancer detection using analysis of exhaled carbonyl compounds

Abstract: Screening using a low-dose CT scan is associated with high cost, repeated radiation exposure, and low accrual. The high sensitivity, convenience, and low cost of breath analysis for carbonyl cancer markers suggests that it has the potential to become a primary screening modality for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 16 publications
1
39
0
Order By: Relevance
“…We also compared LC with benign nodules, with results similar to those from previous studies. 13,14,19,20,26,27 In our previous pilot study of patients from Colorado, we showed that benign pulmonary nodules could be well discriminated from LC by a unique breath print. 25 The nanoarray sensors could also discriminate between adenocarcinomas and SCCs and between early-stage and advanced disease.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…We also compared LC with benign nodules, with results similar to those from previous studies. 13,14,19,20,26,27 In our previous pilot study of patients from Colorado, we showed that benign pulmonary nodules could be well discriminated from LC by a unique breath print. 25 The nanoarray sensors could also discriminate between adenocarcinomas and SCCs and between early-stage and advanced disease.…”
Section: Discussionmentioning
confidence: 88%
“…13 Recently, by using mass spectrometry, Schumer et al found that four volatile carbonyl compounds could be sensitive markers for LC, with specificity proportional to the number of the elevated markers. 14 Nanoarray sensors allow the identification of a large number of VOCs through precise monitoring of changes in electrical resistance. When pattern recognition methods and classification techniques are used, the combined response from all sensors establishes a volatolomic signature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to urinary samples [133135], other noninvasive and low-cost tools for the screening of oxidative stress, such as salivary [136138] or exhaled breath [139141] analysis, have been proposed. However, it has been reported that creatinine urinary markers are not suitable in patients with impaired renal function [135].…”
Section: Markers Based On Ros-induced Modificationsmentioning
confidence: 99%
“…2,3 In brief, the e-nose works by identifying fingerprints, or breathprints, defined by the activation of gas sensors exposed to volatile organic compounds (VOCs) that are markers of the cellular metabolism which are found in the exhaled breath but also in other organic fluids. 2,3 Several investigators worldwide have already published the results of their preliminary studies yielding high accuracy for the e-nose in distinguishing between malignant and benign pulmonary nodules as well as the potential to identify an adenocarcinoma histotype and even EGFR status. 2,3 The Historic Background of E-Nose Technology…”
mentioning
confidence: 99%
“…2,3 Several investigators worldwide have already published the results of their preliminary studies yielding high accuracy for the e-nose in distinguishing between malignant and benign pulmonary nodules as well as the potential to identify an adenocarcinoma histotype and even EGFR status. 2,3 The Historic Background of E-Nose Technology…”
mentioning
confidence: 99%